Physical, chemical, microbiological and sensory characteristics of a probiotic beverage produced from different mixtures of cow's milk and soy beverage by Lactobacillus acidophilus La5 and yoghurt culture - Šertović, Edina (Array, 2019)
The aim of this paper is to determine nutritive, functional, microbiological and sensory properties of probiotic beverages produced from different volume ratios of cow's milk and soy beverage (25:75, 50:50 and 75:25). Pure cow’s milk and soy beverage served as control samples. Fermentation was performed at 43 °C by a combined culture consisting of the probiotic strain Lactobacillus acidophilus La5 and yoghurt culture. Viable counts of La5 strain in the produced beverages ranged from 7.52 to 8.20 log CFU/mL, which is above the probiotic minimum (106 CFU/mL). Lactic acid was the most prevalent organic acid in all samples (660.1 to 1003.0 mg/100 mL). The fatty acid profiles of fermented beverages were as follows: the mass fraction of saturated fatty acids was 22.2–82.7 %, of unsaturated fatty acids 22.3–77.8 % and of polyunsaturated fatty acids 15.5–65.9 %. The main soy sugars were transformed well (80 % stachyose and 50 % raffinose conversion) into lactic acid during fermentation. Functional probiotic beverages were successfully produced from different volume ratios of cow's milk and soy beverage by L. acidophilus La5 and yoghurt culture. Mixing cow's milk with soy beverage significantly improved the sensory properties of the product, especially its smell, taste and colour. The acceptability test showed good acceptance by potential consumers of all fermented beverage samples except for the sample made from 100 % soy beverage. In the end, the obtained results represent a good basis for optimisation of the ideal volume ratios of cow's milk and soy beverage for production of fermented beverages characterised by good viability of probiotic bacteria as well as by good functional, nutritive and sensory characteristics.